And the National Anti-Corruption Policy? Well, Thank You... - Kundmüller Caminatti, Franz (2006)
This article addresses the issue of corruption and, although it does not seek to cover all aspects of the issue, it does aim to contribute to the creation of a national policy that is aligned with recent international anti-corruption regulations. This study presents data on the level of corruption worldwide, detailing how it has progressed during globalization, and analyzing its impact on democracy, particularly in Latin America. It also assesses the role of the United Nations Convention against Corruption (UNCAC) and the perspective of the Asia-Pacific Economic Cooperation (APEC) in fighting corruption. The conclusion drawn by the author is that we need a collaborative global approach to understand and combat corruption from all angles.